2016
DOI: 10.7189/jogh.06.020404
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impact of quality improvement interventions on the quality of sick child care provided by Health Extension Workers in Ethiopia

Abstract: BackgroundEthiopia has scaled up integrated community case management of childhood illness (iCCM), including several interventions to improve the performance of Health Extension Workers (HEWs). We assessed associations between interventions to improve iCCM quality of care and the observed quality of care among HEWs.MethodsWe assessed iCCM implementation strength and quality of care provided by HEWs in Ethiopia. Multivariate logistic regression analyses were performed to assess associations between intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…Child health interventions can be delivered at health facility and community levels. Particularly in resource limited settings, community-based services need to be strengthened so that child health interventions can be delivered by appropriately trained and supported community health workers, who extend the health services to the local community [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Child health interventions can be delivered at health facility and community levels. Particularly in resource limited settings, community-based services need to be strengthened so that child health interventions can be delivered by appropriately trained and supported community health workers, who extend the health services to the local community [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…We aim to measure the extent to which interventions are actually implemented and whether the processes are in place and producing the outputs expected. Definitions and the elements of implementation strength emerged initially from the work of Johns Hopkins University Institute for International Programs and Informed Decisions for Actions in Maternal and Newborn Health [ 9 , 10 , 42 , 43 ].…”
Section: Results: the Pathway And Its Applicationsmentioning
confidence: 99%
“… 29 Studies conducted in Ethiopia on supportive supervision and performance review and clinical mentorship meetings have also shown that these can be effective means of improving services provided by HEWs. 30 The OHEP intervention had no effect on the supervision and the performance review and clinical mentoring meetings provided for HEWs. The quality of iCCM services measured at baseline was low, and it is unlikely to have been improved by the training, supervision and infrequent clinical mentoring supported by OHEP.…”
Section: Discussionmentioning
confidence: 96%